Intersectoriality, the health of the elderly and the exercise orientation service: A documental analisys - Camargo, Leonardo Perovano; Borges, Carlos Nazareno Ferreira (Seven Editora, 2024)
The Health Academy Program, instituted by Brazilian Ministry of Health’s in 2011, had its origins in some previous municipal programs, like the Exercise Orientation Service (SOE) from Vitória/ES, implanted in 1990. The population aging is a worldwide phenomenon that requires adaptations in the public policies for the elderly population. The National Health Promotion Policy points to intersectorality as an institutional element and form of management that enhances public health services. In addition, social participation, one of the elements of intersectoriality, is as a relevant aspect for the protection and promotion of active life for the elderly. Thus, despite the pioneering of SOE as public policy for health promotion, still not clear how the intersectoriality influence the management of the program. Thus, this study aimed to analyze the elements of intersectoriality, through a documentary analysis, related to the health of the elderly population, inside the Exercise Orientation Service (SOE). Richardson’s documentary analysis was used as the methodology of research. Among Dye’s models of political analysis, the beginning of SOE were classified as the elite model and currently acting as the incremental model, which are variations on the past, applying small improvements in already consolidated policies, to avoid political conflicts and spending on new or large reformulations. It is concluded that SOE, despite being a vanguard public policy and national reference, still has incipient intersectoral relations, classified as horizontal governmental articulations, which is an embryonic intersectoriality, opening way to build a public policy with more reach and quality. DOI:https://doi.org/10.56238/sevened2024.016-029